2013
DOI: 10.1177/003335491312800109
|View full text |Cite
|
Sign up to set email alerts
|

Sorrell v. IMS Health Inc.: Data Mining of Pharmacy Records and Drug Marketing as Free Speech

Abstract: One of the most important challenges facing public health agencies is how best to regulate health-care industry practices that carry public health implications. A crucial question, however, is the extent to which the U.S. Constitution imposes limits on the regulatory powers of public health, when the industry conduct in question involves what the law considers speech. The following article discusses the implications of a recent U.S. Supreme Court decision for public health policy and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Limitations of our study include recall bias (questions were asked retrospectively, both in the postnatal period for PRAMS and for CUBS) as well as self-report and mode bias—some mothers may report certain behaviors more or less willingly than other mothers based on their experiences or they may be more or less willing to disclose certain behaviors during a mail survey [ 38 , 39 ]. Our outcome of childhood obesity was based on self-reported measurements by the mother and previous studies have found some misclassification of child weight category based on parental report, with under estimates of child heights resulting in upward bias in obesity prevalence estimates [ 40 , 41 ]. Some factors that we examined had missing values, including 16.5% of respondents missing information on the outcome of childhood BMI and 10.5% missing information on paternal education.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of our study include recall bias (questions were asked retrospectively, both in the postnatal period for PRAMS and for CUBS) as well as self-report and mode bias—some mothers may report certain behaviors more or less willingly than other mothers based on their experiences or they may be more or less willing to disclose certain behaviors during a mail survey [ 38 , 39 ]. Our outcome of childhood obesity was based on self-reported measurements by the mother and previous studies have found some misclassification of child weight category based on parental report, with under estimates of child heights resulting in upward bias in obesity prevalence estimates [ 40 , 41 ]. Some factors that we examined had missing values, including 16.5% of respondents missing information on the outcome of childhood BMI and 10.5% missing information on paternal education.…”
Section: Discussionmentioning
confidence: 99%
“…24 Following the Court's decision in favor of IMS, however, the diversionary practices described by Justice Breyer continued apace as a constitutionally protected activity, with little recourse for lawmakers seeking to regulate pharmaceutical marketing by means of proactive data policies. 25 As Mallinckrodt's trajectory illustrates, the continued recycling of prescribing data in drug detailing created particularly perverse incentives in the opioid market. The Mallinckrodt documents record more than one million sales visits to prescribers, distributors, or pharmacies between 2008 and 2015, but they also reveal how sales teams exploited IMS data to direct the bulk of their resources toward a small number of top opioid prescribers.…”
Section: Eyes On the Scriptmentioning
confidence: 99%